Synergy of contemporary architecture and materials science - Rychkov, Petro; Lushnikova, Nataliya (Budownictwo i Architektura / Civil and Architectural Engineering, 2017)
The article gives coverage on the levels of synergetic interaction between architecture and materials science. There are discussed some main benefits and challenges of such kind of synergism. There are separated different levels of synergy. Upon analysis of the industrial and postindustrial age achievements in both of the areas, there can be determined three main levels of synergetic interrelations: inspiration, application, participation. As novel materials and selection tools develop and the area of their possible architectural application increases, the synergistic effect s are predicted to strengthen.